Life-Threatening Bleeding in Children: A Prospective Observational Study. Issue 11 (12th May 2021) - Leonard, Julie C.; Josephson, Cassandra D.; Luther, James F.; Wisniewski, Stephen R.; Allen, Christine; Chiusolo, Fabrizio; Davis, Adrienne L.; Finkelstein, Robert A.; Fitzgerald, Julie C.; Gaines, Barbara A.; Goobie, Susan M.; Hanson, Sheila J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: The purpose of our study was to describe children with life-threatening bleeding. DESIGN: We conducted a prospective observational study of children with life-threatening bleeding events. SETTING: Twenty-four childrens hospitals in the United States, Canada, and Italy participated. SUBJECTS: Children 0–17 years old who received greater than 40 mL/kg total blood products over 6 hours or were transfused under massive transfusion protocol were included. INTERVENTIONS: Children were compared according bleeding etiology: trauma, operative, or medical. MEASUREMENTS AND MAIN RESULTS: Patient characteristics, therapies administered, and clinical outcomes were analyzed. Among 449 enrolled children, 55.0% were male, and the median age was 7.3 years. Bleeding etiology was 46.1% trauma, 34.1% operative, and 19.8% medical. Prior to the life-threatening bleeding event, most had age-adjusted hypotension (61.2%), and 25% were hypothermic. Children with medical bleeding had higher median Pediatric Risk of Mortality scores (18) compared with children with trauma (11) and operative bleeding (12). Median Glasgow Coma Scale scores were lower for children with trauma (3) compared with operative (14) or medical bleeding (10.5). Median time from bleeding onset to first transfusion was 8 minutes for RBCs, 34 minutes for plasma, and 42 minutes for platelets. Postevent acute respiratory distress syndrome (20.3%) and acute kidney injury (18.5%) were common. Twenty-eight–day mortality was 37.5% and higher among children with medical bleeding (65.2%) compared with trauma (36.1%) and operative (23.8%). There were 82 hemorrhage deaths; 65.8% occurred by 6 hours and 86.5% by 24 hours. CONCLUSIONS: Patient characteristics and outcomes among children with life-threatening bleeding varied by cause of bleeding. Mortality was high, and death from hemorrhage in this population occurred rapidly.